Invasive cribriform carcinoma of the breast detected incidentally on computed tomography: A case report. Issue 12 (15th December 2021) - Adachi, Yasuhiro; Katsuki, Takefumi; Sasaguri, Takakazu; Hirata, Keiji; Nagata, Naoki
Abstract: Invasive cribriform carcinoma is a rare type of invasive breast carcinoma, and a few cases have been reported. Its features are a cribriform pattern resembling the histological structures of cribriform ductal carcinoma in situ and an excellent prognosis. However, the extent of progress for intraductal extension must be carefully evaluated. Abstract : Immunohistological findings of this ICC. (A)Tumor islands have no positive cells for CD10, whereas myoepithelial cells are preserved around the DCIS. (B) No CD10‐positive cells were found in the invasive cribriform cancer area. (C) ER is strongly stained. (D) PgR is strongly stained. (E) HER2 expression is judged as score 0. (F) Ki‐67 staining is observed in 7% of all cells.